2016
DOI: 10.18632/oncotarget.9470
|View full text |Cite
|
Sign up to set email alerts
|

Functional role and tobacco smoking effects on methylation ofCYP1A1gene in prostate cancer

Abstract: Cytochrome P450 (CYP) 1A1 is a phase I enzyme that can activate various compounds into reactive forms and thus, may contribute to carcinogenesis. In this study, we investigated the expression, methylation status, and functional role of CYP1A1 on prostate cancer cells. Increased expression of CYP1A1 was observed in all cancer lines (PC-3, LNCaP, and DU145) compared to BPH-1 (P < 0.05); and was enhanced further by 5-aza-2′-deoxycytidine treatment (P < 0.01). Methylation-specific PCR (MSP) and sequencing of bisul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
5
12
0
Order By: Relevance
“…CYP1A1 is a member of the phase I cytochrome P450 family, which is highly active in the liver, acting on the metabolic activation of HAAs [ 28 ]. Similar to NAT2 , CYP1A1 mRNA is also expressed in prostate tissue [ 48 50 ]. CYP1A1 in individuals harboring the mutant G allele (GA or GG genotype) in exon 7, which substitutes valine for isoleucine, has a higher catalytic activity compared to that found in individuals who are homozygous AA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A1 is a member of the phase I cytochrome P450 family, which is highly active in the liver, acting on the metabolic activation of HAAs [ 28 ]. Similar to NAT2 , CYP1A1 mRNA is also expressed in prostate tissue [ 48 50 ]. CYP1A1 in individuals harboring the mutant G allele (GA or GG genotype) in exon 7, which substitutes valine for isoleucine, has a higher catalytic activity compared to that found in individuals who are homozygous AA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…(chr11:2154089-2154542) is part of a CpG island and shore but it is located in the gene body. DNA methylation of CYP1A1 was associated with exposure to dioxin and external pollutants in different studies (Mitsui et al, 2014;Okino and Whitlock, 1995). DNA methylation of IGF2 was associated with environmental chemical exposure (Hou et al, 2012), while a previous study reported that exposure of mouse preimplantation embryos to dioxin alters the methylation status of imprinted genes H19 and IGF2 (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…In this context the aim of the present study was to investigate the DNA methylation patterns of two candidate genes, CYP1A1 and IGF2 in order to address the question whether exposure to dioxin in Vietnam is associated with persistent differences in methylation as previously suggested (Manikkam et al, 2012;Skinner et al, 2013) including, for the first time, a very detailed description of historical data (in terms of number of spray runs and spray dates for each district). The rationale beyond the selection of the two genes was the following: CYP1A1 belongs to the cytochrome 450 family, which is involved in the metabolism of various molecules and chemicals within cells (Ko et al, 1996;Mitsui et al, 2014;Okino and Whitlock, 1995;Whitlock et al, 1997) . Dioxin is known to be a CYP1A1 inducer (Tsyrlov and Pokrovsky, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have shown that the upregulation of CYP1A1 results in the malignancy of various types of tumor cells . CYP1A1 was found to have an oncogenic role in prostate cancer, indicating that CYP1A1 could be a promising target for prostate cancer therapeutics, and to promote breast cancer proliferation and survival through the suppression of AMPK signaling . In addition, CYP1A1 protected against nonalcoholic fatty liver disease (NAFLD) and hepatic inflammation caused by a western diet plus benzo [a] pyrene in mice, indicating that CYP1A1 protected against NAFLD pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Agonists such as β‐NF and TCDD facilitate AhR binding to the xenobiotic‐responsive element (XRE) and consequently upregulate the expression of CYP1A1 . In addition, the XRE is a conserved sequence among the CYP1 subfamily, and up to 10 high‐affinity binding sites for the AhR complex have been identified in the human CYP1A1 promoter . Moreover, multiple copies of consensus XRE sequences are found in the 5'‐flanking region of CYP1A1 .…”
Section: Introductionmentioning
confidence: 99%